2007
DOI: 10.1051/mbcb/2007019
|View full text |Cite
|
Sign up to set email alerts
|

Enquête sur l’utilisation des anesthésiques locaux par les chirurgiens dentistes exerçant en Alsace

Abstract: RÉSUMÉObjectifs : L'objectif de cette enquête était d'identifier les pratiques et les usages des anesthésiques locaux lors des différents types d'actes par les chirurgiens dentistes exerçant en Alsace. Matériels et méthodes : L'ensemble des praticiens exerçant en Alsace (1 500) ont reçu un questionnaire de quatre pages par différents moyens. 311 questionnaires ont été renvoyés (20.7 %) et 308 ont été retenus. Les réponses ont été enregistrées dans un tableau Excel après anonimisation. L'enquête a été conduite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The study conducted by Corbati I. et al in the United Kingdom reported that 20% of dentists used anesthesia without vasoconstrictors for uncontrolled diabetic patients. Another study conducted by A. Vander Auwera et al showed that only 25.3% of participants choosed anesthesia without vasoconstrictors among this type of patient [14] [15].…”
Section: Discussionmentioning
confidence: 92%
“…The study conducted by Corbati I. et al in the United Kingdom reported that 20% of dentists used anesthesia without vasoconstrictors for uncontrolled diabetic patients. Another study conducted by A. Vander Auwera et al showed that only 25.3% of participants choosed anesthesia without vasoconstrictors among this type of patient [14] [15].…”
Section: Discussionmentioning
confidence: 92%